SCIENTIFIC RESEARCH METHODOLOGY AS A GENERAL APPROACH AND PERSPECTIVE OF THE RESEARCH PROCESS - MARHASOVA Viktoriіa; GARAFONOVA, Olga; DERII, Zhanna; RUDENKO, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the methodology of scientific research as a general approach and perspective of the research process. Methodology in research is defined as a systematic method of solving a research problem by collecting data using various methods, providing an interpretation of the collected data, and drawing conclusions about the research data. Essentially, research methodology is a scheme of research or study. A research method is usually seen as a means of collecting or generating data. Traditionally, research methods are divided into quantitative methods (ie, surveys, questionnaires), qualitative methods (ie, interviews, focus groups), or some combination of both in mixed methods research. Research methods vary widely and may include written, visual, verbal, observational, artistic, and active strategies. Scientific research refers to research that collects data using systematic methods and strategies. Data collection, data interpretation and evaluation have a scientific and systematic basis. When conducting scientific research, the researcher must plan the research and determine the methodology. According to the methods used to collect data, scientific research can be classified into different categories such as observation and experiment. The process of scientific research requires a person to devote a lot of time and effort to the process of planning and experimenting in order to find accurate and verified results. Scientific research cannot be conducted in limited time because it will only lead to false conclusions that are of no value to the organization.Conducting research has been a necessary step in human and scientific discovery and evolution. Through research, mankind has been able to solve and successfully find solutions to enormous problems through thinking and reasoning. Conducting research is a time-consuming and exhausting process, as one constantly faces obstacles in trying to get accurate results to discover a solution. However, many great minds have constantly strived for perfection and have helped solve many of the world’s troubling problems and issues through this tedious process. Hence, it has been argued time and time again that research is necessary for progress, improvement and evolution. Understanding the different research methods available, their applicability, advantages, and disadvantages is essential to making an informed decision about the best methodology.